Salmonella enterica Serovar Dublin from Cattle in California from 1993–2019: Antimicrobial Resistance Trends of Clinical Relevance - Heather M. Fritz; Richard V. Pereira; Kathy Toohey-Kurth; Edie Marshall; Jenna Tucker; Kristin A. Clothier (Antibiotics, 2022)
Salmonella enterica subsp. enterica serovar Dublin (S.Dublin) is a cattle-adapted pathogen that has emerged as one of the most commonly isolated and multidrug resistant (MDR) serovars in cattle. S.Dublin may be shed in feces, milk, and colostrum and persist in asymptomatic cattle, leading to spread and outbreaks in herds. Though infections with S.Dublin in humans are rare, they are frequently severe, with extraintestinal spread that requires hospitalization and antimicrobial therapy. To determine minimum inhibitory concentration (MIC) and antimicrobial resistance (AMR) patterns and trends in cattle in California, broth microdilution testing was performed on 247 clinical S. Dublin isolates recovered from cattle at the California Animal Health and Food Safety Laboratory System (CAHFS) over the last three decades (1993–2019). Mean MICs and classification of resistance to antimicrobial drugs using a clinical livestock panel and the National Antimicrobial Resistance Monitoring System (NARMS) Gram-negative drug panels were utilized to assess prevalence and trends in AMR. Findings indicate an increase in AMR for the years 1993 to 2015. Notably, compared to the baseline year interval (1993–1999), there was an increase in resistance among quinolone and cephalosporin drugs, as well as an increased number of isolates with an MDR profile.